2022
DOI: 10.3389/ffgc.2022.941851
|View full text |Cite
|
Sign up to set email alerts
|

Structural complexity and primary production resistance are coupled in a temperate forest

Abstract: The capacity of forests to resist structural change and retain material legacies–the biotic and abiotic resources that persist through disturbance–is crucial to sustaining ecosystem function after disturbance. However, the role of forest structure as both a material legacy and feature supporting carbon (C) cycling stability following disturbance has not been widely investigated. We used a large-scale disturbance manipulation to ask whether legacies of lidar-derived canopy structures drive 3-year primary produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…This traits-production relationship held across a wide range of disturbance severity levels from 0 to 85% gross defoliation, suggesting a conserved ecological mechanism in forests experiencing partial to near total stem mortality. Our findings reinforce the critical role of material legacies, or the biotic and abiotic resources remaining after disturbance (Niedermaier et al, 2022). Although prior work attributed the stimulation of subcanopy production following disturbance to greater light availability (Muscolo et al, 2014;Stuart-Haëntjens et al, 2015;Kennard et al, 2020), our 4-year analysis demonstrates that multiple leaf functional traits responded to disturbance before deterioration of the upper canopy.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This traits-production relationship held across a wide range of disturbance severity levels from 0 to 85% gross defoliation, suggesting a conserved ecological mechanism in forests experiencing partial to near total stem mortality. Our findings reinforce the critical role of material legacies, or the biotic and abiotic resources remaining after disturbance (Niedermaier et al, 2022). Although prior work attributed the stimulation of subcanopy production following disturbance to greater light availability (Muscolo et al, 2014;Stuart-Haëntjens et al, 2015;Kennard et al, 2020), our 4-year analysis demonstrates that multiple leaf functional traits responded to disturbance before deterioration of the upper canopy.…”
Section: Discussionsupporting
confidence: 79%
“…Although a number of studies have examined community trait responses to severe disturbances such as fire (Pausas et al, 2004;Huerta et al, 2021;Pellegrini et al, 2021), the timing and magnitude of plant functional trait change across more extensive gradients of severity, as well as how these shifts may relate to production, remains unclear (Diaz et al, 2007;Biswas and Mallik, 2010;Herben et al, 2018). Recent work from FoRTE has shown that growth of surviving subcanopy and canopy trees was able to fully compensate for reductions in canopy area up to 3 years following disturbance initiation (Grigri et al, 2020;Niedermaier et al, 2022). This stimulated subcanopy growth (i.e., increased carbon uptake of this stratum) coupled with declines in soil respiration (i.e., carbon loss from the system) that were proportional to disturbance severity and sustained through time (Mathes et al, 2023) enabled the forest to maintain remarkable NPP stability at even the highest levels of disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To describe the vertical change in forest fuel density, we calculated the VAI from the ground surface to the top of the canopy of each plot. The VAI describes the amount of vegetation area per unit area in the vertical profiles of a stand [29,50], which allows for the quantification of the density distribution and relative position of fuel within the stand using point cloud data [29]. We took 1 cm as the basic unit of stratification in the vertical direction and then counted the vegetation area of each layer.…”
Section: Vegetation Area Index (Vai) and Vegetation Coverage Of Diffe...mentioning
confidence: 99%